Effects of Inversion Layer on The Atmospheric Pollutant Dispersion from A High Chimney - Zai, Fidelis Nofertinus; Gunawan, Agus Yodi (IndoMS, 2023)
An inversion layer is a layer in the lower atmosphere at a certain height through which there is no transport of pollutants. It plays as a significant factor in the formation of air pollutants where they are trapped. In this paper, a mathematical model describing an atmospheric pollutant dispersion from a high chimney in the presence of an inversion layer is constructed. The aim of the model is to predict the concentration of pollutants at ground level. The advection-diffusion equation governs the concentration of a pollutant released into the air. An analytical solution procedure via the integral transforms is presented for the steady-state case. Solutions are entirely determined by two parameters, i.e., the source strength emanating from the chimney and the height of the inversion layer. The pollutant concentration on the ground level with some multiple source formations will be explored, and also for various values of inversion layer height. Results show that the lower the inversion layer, the higher the pollutant concentration on the ground level is.